THE ROLE OF INTERNAL CONTROL AND COMPENSATION APPROPRIATENESS IN SHAPING ANTI-FRAUD BEHAVIOR: THE MODERATING EFFECT OF THE BYSTANDER EFFECT IN COOPERATIVES IN KUDUS REGENCY - Sri Mulyani; Nita Andriyani Budiman; Dina Lusianti; Mamik Indaryani (Jurnal Bisnis dan Akuntansi, 2026)
This study aims to examine the influence of internal control and compensation appropriateness on anti-fraud behavior, with the bystander effect acting as a moderating variable in cooperatives in Kudus Regency. This study draws on the Fraud Triangle Theory, which explains that fraud arises from pressure, opportunity, and rationalization. Internal control is associated with reducing opportunity, while compensation appropriateness alleviates pressure. The bystander effect is conceptualized as a social mechanism that reinforces silence and weakens the effectiveness of these structural mechanisms. This study employed a quantitative survey approach using data from 351 cooperative managers, including supervisors, secretaries, and treasurers. Data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM). The results show that internal control and compensation appropriateness have a positive effect on anti-fraud behavior, while the bystander effect weakens these relationships. This study contributes to the anti-fraud behavior literature by integrating structural and behavioral perspectives, highlighting that the effectiveness of formal control mechanisms depends on social dynamics within the organization.